2017
DOI: 10.1108/jmd-11-2015-0162
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational justice on job performance

Abstract: Purpose The purpose of this paper is to propose two models: the first examines the impact of different dimension of justice (distributive, procedural and interactional) on job performance taking into consideration the mediating role of affective commitment and the second model utilizes the notion of overall justice to predict job performance considering the mediating role of affective commitment. Design/methodology/approach This study was conducted with a sample group of 343 employees working within French s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
120
3
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(152 citation statements)
references
References 81 publications
17
120
3
12
Order By: Relevance
“…This supports the justice -performance relationship found in literature (Swalhi et al 2017;Devonish & Greenidge, 2010) and supports the results found in similar cultures like Saudi Arabia and Jourdan where organisational justice was found to significantly affect OCB (Elamin & Tlaiss, 2015;Al-Quraan & Khasawneh, 2017). However, to the best of authors' knowledge this current research is the first research that investigates the effect of perceived organisational justice on the three dimensions of performance within an Arab context.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This supports the justice -performance relationship found in literature (Swalhi et al 2017;Devonish & Greenidge, 2010) and supports the results found in similar cultures like Saudi Arabia and Jourdan where organisational justice was found to significantly affect OCB (Elamin & Tlaiss, 2015;Al-Quraan & Khasawneh, 2017). However, to the best of authors' knowledge this current research is the first research that investigates the effect of perceived organisational justice on the three dimensions of performance within an Arab context.…”
Section: Discussionsupporting
confidence: 87%
“…DJ was developed by Adams (1963) who suggested that fairness is evaluated as a result of the ratio between employees' inputs and their outputs that is in contrast with the perceived inputs and outputs of comparable employees (Devonish & Greenidge, 2010). Procedural Justice (PJ) refers to the perceived fairness of the decision making process used to determine the obtained outcomes (Nowakowski & Conlon, 2005), as employees concern about the procedures through which they got their outcomes as much as the outcomes themselves (Swalhi et al 2017). Interactional Justice (IJ) emerged as a reflection of the emphasis on the 'human element' in the organisational context (Devonish & Greenidge, 2010).…”
Section: Organisational Justice (Oj)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they seek out those with the necessary skills and knowledge and invest in training to help them improve their performance. Previous research has documented such efforts (Medina‐Garrido, Biedma‐Ferrer, & Ramos‐Rodríguez, ; Swalhi et al, ). Given the growing complexity of job‐related tasks, however, managers are finding it ever more challenging to manage employees’ performance.…”
Section: The Link Between Engagement and Performancementioning
confidence: 99%
“…As frontline staff, nurses play a significant role in how patients perceive service quality and their level of satisfaction with the facility where they receive treatment. Moreover, the performance of nurses not only significantly affects the provision of quality healthcare services, but also their own career development (Swalhi, Zgoulli, & Hofaidhllaoui, ).…”
Section: Introductionmentioning
confidence: 99%